2013
DOI: 10.1016/j.ccr.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

NEK2 Induces Drug Resistance Mainly through Activation of Efflux Drug Pumps and Is Associated with Poor Prognosis in Myeloma and Other Cancers

Abstract: SUMMARY Using sequential gene expression profiling (GEP) samples, we defined a major functional group related to drug resistance that contains chromosomal instability (CIN) genes. One CIN gene in particular, NEK2, was highly correlated with drug resistance, rapid relapse, and poor outcome in multiple cancers. Over-expressing NEK2 in cancer cells resulted in enhanced CIN, cell proliferation and drug resistance, while targeting NEK2 by NEK2 shRNA overcame cancer cell drug resistance and induced apoptosis in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
379
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 247 publications
(412 citation statements)
references
References 48 publications
21
379
2
1
Order By: Relevance
“…Viridin analogs, which are highly specific inhibitors of Nek2, can induce centrosome disruption and inhibit cancer cell growth in vitro (40). Other recent work has indicated that Nek2 silencing can induce apoptosis of cells that show chromosomal instability but not of cells with a normal karyotype (41,42). Our study provides in vivo validation of the concept that Nek2 is important for tumor growth in both primary and secondary sites, and strengthens the rationale underlying the growing efforts to develop specific therapeutic inhibitors against this kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Viridin analogs, which are highly specific inhibitors of Nek2, can induce centrosome disruption and inhibit cancer cell growth in vitro (40). Other recent work has indicated that Nek2 silencing can induce apoptosis of cells that show chromosomal instability but not of cells with a normal karyotype (41,42). Our study provides in vivo validation of the concept that Nek2 is important for tumor growth in both primary and secondary sites, and strengthens the rationale underlying the growing efforts to develop specific therapeutic inhibitors against this kinase.…”
Section: Discussionmentioning
confidence: 99%
“…XIA LIU More recently, NEK2 has become important since two studies indicate that high expression of NEK2 induces drug resistance in multiple myeloma (21,22). However, despite these study, the research on NEK2 in regards to drug resistance in cancers is still limited, and its relationship with drug resistance in ovarian cancer has never been reported.…”
Section: Upregulation Of Nek2 Is Associated With Drug Resistance In Omentioning
confidence: 99%
“…The target gene, NEK2, which is closely associated with drug resistance in multiple myeloma (21,22) was selected for bioinformatic analysis. …”
Section: Methodsmentioning
confidence: 99%
“…9,[24][25][26] The details were described in the supplemental Data (available on the Blood Web site).…”
Section: Methodsmentioning
confidence: 99%
“…24 Briefly, 10 000 MM cells were seeded in 0.33% agar cultures. The colonies were fed with medium in the presence or absence of drugs; after 3 weeks, the plates were imaged and colony numbers were counted by ImageJ.…”
Section: Clonogenic Formation Assaymentioning
confidence: 99%